Metformin as an adjuvant option for systemic treatment of breast cancer - D.I. Avierin; V.F. Zavizion (Medičnì Perspektivi)
The modification of the used and development of new treatment regimens significantly improved the overall, recurrence-free survival and quality of life of patients with malignant oncological diseases. Recently, drugs used in non-oncological pathology have been introduced into cancer treatment regimens. This phenomenon is associated with a better understanding of the biology of tumor cells and the mutations that can change this biology. Metformin is actively researched in terms of the treatment of various oncological diseases. For the most part, the modification of the neoadjuvant treatment regimen for early or locally advanced stages of breast cancer results in a less traumatic variant of surgical procedure, thereby increasing recurrence-free survival. The aim is to systematize the data on the possibilities of the antitumor metformin usage for neoadjuvant treatment of breast cancer and to study the results of clinical and morphological effectiveness of the treatment by reviewing the literature. A search of PubMed from February 2023 showed 258 results on the antitumor effects of metformin, of which only 159 were published in the last 5 years. On this subject only four clinical studies were carried out, and only one of them pertained to the implementation of metformin in the systemic treatment of breast cancer. For this review, 55 sources of general and specialized information on anticancer effects of metformin were analyzed. It should be noted that approximately 60% of the study results were published more than 5 years ago and primarily focused on the biological, not clinical aspects of metformin usage. Only one study regarding the implementation of metformin for systemic treatment of breast cancer was carried out by Ukrainian scientists. Currently, there are 2 main hypotheses regarding the antitumor effect of metformin. First one is driven by its impact on the metabolic function of cells and energy deficit. Second – the method of regulating the proliferation of tumor cells involves the PIK3 branch of the regulatory cascade of biological reactions in cancer cells. In addition, metformin reduces the development of resistance in breast cancer cells, thus allowing active chemotherapy agents to act in synergism. However, further studies on the effect of metformin used alone or in combination with standard chemotherapy regimens require a more adequate definition of proto-oncogenic mutations and somatic mutation load. However, it should be considered that more aggressive therapy of oncological diseases can be a nosocomial selector of more aggressive clones of the pool of tumor cells. The main questions are whether metformin can be a targeted drug for the treatment of tumor, whether it is appropriate to use it at the time when the manifestation of evolution disturbances of tumor cell is minimal and homogeneity is maximal.